2011
DOI: 10.5539/ach.v4n1p2
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement Effects on Mental Health in Chinese Americans

Abstract: Faith has been shown to serve a protective role in the mental health of African Americans and European Americans. However, little research has examined whether any association exists in Asian Americans. Using the National Latino and Asian American Study dataset, we examined the effect of religious attendance on the mental health of Asian Americans in the United States. The present study focused on Chinese Americans because they are the largest Asian American group. The results revealed that almost 80% of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The current analysis reveals greater discrimination experienced by Christians. Huang, Appel, Ai, and Lin (2012) associated religious attendance, but not discrimination, with depression in Chinese Americans. The potential interaction between ethnic subgroups and religious involvement may further complicate the interpretation of our findings.…”
Section: Discussionmentioning
confidence: 92%
“…The current analysis reveals greater discrimination experienced by Christians. Huang, Appel, Ai, and Lin (2012) associated religious attendance, but not discrimination, with depression in Chinese Americans. The potential interaction between ethnic subgroups and religious involvement may further complicate the interpretation of our findings.…”
Section: Discussionmentioning
confidence: 92%
“…The BSI-18 is a frequently used self-report questionnaire that is designed to measure the current level of psychological distress in adult individuals. It consists of three subscales with each assessing a common psychiatric syndrome, namely somatization (items 1, 4, 7, 10, 13, 16), depression (items 2, 5,8,11,14,17), and anxiety (items 3,6,9,12,15,18). The 18 items are allocated equally across the three subscales, with each examining on a 5-point Likert scale (from 0 = "not at all" to 4 = "extremely") to what extent the respective symptom burdened the respondent during the previous 7 days.…”
Section: Instrumentsmentioning
confidence: 99%
“…Religious involvement and mental health beliefs are often interrelated in their impact on mental health, especially among Asians, due to the close connection between religion and health within their value system ( 10 ). Accordingly, studies have documented a positive effect of religiosity on mental health, for instance, higher self-rated subjective well-being among Chinese Americans with more frequent religious attendance ( 11 ). Some studies, however, have reported the opposite when religiosity interferes with the concept of mental health (care) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have empirically demonstrated that promoting older migrants' participation in community activities is vitally important to achieve longer healthy life expectancy, as well as better quality of life. For example, participating in local religious activities was found to be a benefit to psychological well-being [19][20][21], and actively seeking community healthcare services and other social support can reduce feelings of alienation and isolation [3,22]. Joining social organizations and other programs; attending immigrant language classes and housing services; and obtaining "reciprocal" neighborhood support through childcare, housekeeping, and volunteering can strengthen the sense of belonging and community [2,4,23].…”
Section: Introductionmentioning
confidence: 99%